From isolated 1H-pyrazole cryptand anion receptors to hybrid inorganic–organic 1D helical polymeric anion receptors1. Issue 17 (7th May 2015) - Pitarch-Jarque, Javier; Belda, Raquel; García-España, Laura; Llinares, José M.; Pan, FangFang; Rissanen, Kari; Navarro, Pilar; García-España, Enrique
<x xml:space="preserve">Abstract</x> We report a 1-D helical coordination polymer formed by protonated polyamine 1H-pyrazole cryptands interconnected by Cu2+ metal ions that are able to encapsulate chloride anions behaving as a multianion receptor.